Internet connectivity disruption in India (India) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in India. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: IN-2026-0082. Severity: critical. Confidence: 67%